Características clínico epidemiológicas de fractura de radio distal en pacientes atendidos en el Hospital Regional Docente de Trujillo durante el periodo 2010-2015 - Brocca Loyola, Wilfredo Bernardo (2017)
The objective of the study was to determine the clinical epidemiological characteristics of distal radius fracture in patients treated at the Regional Teaching Hospital of Trujillo during the period 2010-2015. A retrospective descriptive study was conducted, where 42 clinical histories of patients with fracture of Distal radius. It was found that the most frequent age group is between 18 and 27 years old (42.86%); 67% corresponds to the male gender, the majority came from the district of Trujillo (35.71%.), the single status corresponded to 40.47%, the most frequent occupation is that of housewife (28.57%) and the place of occurrence in the majority of cases was the street (38. 10%), 52% suffered affectation of the right side. The most frequent mechanism of production is high energy (71.43%), being 30.95% due to height fall, closed fractures are 88.1% and the most frequent according to the AO classification, is type A2 with 46.51%. The 16.67% was associated with fracture of the ulna and the type of treatment most used is surgical (78.57%). The intrinsic complications found are neurological (7.14%) and vascular (76%)